Daytime Sleepiness and Sleep Quality among Undergraduate Medical Students in Dammam, Saudi Arabia - Mubashir Zafar; Eltigani O. M. Omer; Mohamed Elfatih; Khalid Ansari; Abdul Kareem; Ali Fawaz; Reem Fares; Wadha Saad (Indian Journal of Medical Specialities)
Introduction: Daytime sleepiness and poor sleep quality are common among medical students. The objective of the study is to determine the prevalence of daytime sleepiness and sleep quality and the associated risk factors among medical students in medical college of Dammam, Saudi Arabia. Materials and Methods: It was a cross-sectional study and 149 medical students were selected through stratified random sampling techniques. The Pittsburgh Sleep Quality Index was used to assess the sleep pattern and Epworth Sleepiness Scale was used to measure daytime sleepiness. Association of sleep quality and daytime sleepiness with its risk factors were determined through regression analysis. Results: Students suffering from severe disorder of sleep quality and daytime sleepiness were 30.9% and 34.9%, respectively. In the multivariate analysis after the adjustment of covariates, males (odd ratio [OR]: 1.43, confidence interval [CI]: 1.16–1.95) (P = 0.035) and students who smoke cigarettes (OR: 1.62, CI: 1.18–2.11) (P = 0.045) were at higher risk of having severe daytime sleepiness. First academic year students were more than five times (OR: 5.34, CI: 1.30–12.58) (P = 0.042) and students who had low academic score (grade point average) were more than three times (OR: 3.13, CI: 1.28–4.87) (P = 0.035) likely associated with severe sleep quality disorder. Conclusion: The majority of students had suffered from poor sleep quality and daytime sleepiness. Male gender, smoking, academic score, and academic years were the major predictors for poor sleep quality and daytime sleepiness. There is a need for awareness and counseling among students to reduce the sleep disorder burden.